2020
DOI: 10.3390/ani10061030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Milk and Rumen Microbiome Diversity of Yak, Impacting by Herbage Grown at Different Phenological Periods on the Qinghai-Tibet Plateau

Abstract: To estimate how native herbage of three different phenological periods modify rumen performance and milk quality of yak grazing alpine meadow. In this study, milk composition and the diversity of the rumen microbial community were measured in 12 full-grazing female yaks on the Qinghai-Tibet Plateau (QTP). The nutrient composition of three phenological periods was determined: Vegetative stage (VS), bloom stage (BS), and senescent stage (SS). High-throughput sequencing of the bacterial 16S rRNA gene was used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
(66 reference statements)
2
30
0
Order By: Relevance
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Ruminal contents (liquid and particulate herbage material) were collected using an oral stomach tube from the 24 yaks selected. This method has been used extensively in previous studies [16,22]. The first 50 mL of rumen fluid was discarded to avoid contamination from previous animas or its own saliva; this was followed by collection of 50 mL rumen fluid from each animal prior to grazing in the morning, and immediate pH measurement by pH meter (Model 144 PB-10, Sartorius Co., Germany).…”
Section: Sampling Of Rumen Contents and Measurement Of Fermentation Vmentioning
confidence: 99%
“…All animals in this experiment continued to graze on natural grass after collecting rumen fluid and were in good health condition. Samples (approximately 50 mL) were collected using an oral stomach tube as described by Fan et al (2020) [55]. The first 50 mL of rumen fluid was discarded to avoid contamination from previous animas or its own saliva [4]; this was followed by collection of 50 mL rumen fluid from each animal, and immediate pH measurement by pH meter (Model 144 PB-10, Sartorius Co., Germany).…”
Section: Sampling Of Rumen Digesta and Analyses Of Fermentation Parammentioning
confidence: 99%